PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KELURAHAN LAPAI KECAMATAN NGAPA KABUPATEN KOLAKA UTARA - Sukma, Sukma; Kurniawan, Agung Widhi; Ruma, Zainal (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This study aims to test and find out whether the Work Discipline variable has an effect on employee performance at the Lapai Village Office. The population in this study was a total of 20 employees while the sample in this study was taken from a total population of 20 employees. Questionnaire is a data collection technique used. The collected data were analyzed and then entered into a simple linear regression equation. The findings in this study indicate that partially the Work Discipline variable has a positive effect with a coefficient value of 1.023 (positive) and it is significant on employee performan ce at the Lapai Village Office, Ngapa District, Kolaka Utara Regency, which means if work discipline is increased it will improve employee performance and contrarily. This is evidenced by the obtained value of t arithmetic > t table (2.509 > 1.72913) and the significance value at 5% level is smaller (0.022 < 0.05). So that the hypothesis proposed in this study is accepted.